Socioeconomic inequalities in type 2 diabetes among different population subgroups. (30th September 2020) - Safieddine, B; Sperlich, S; Beller, J; Lange, K; Epping, J; Tetzlaff, J; Tetzlaff, F; Geyer, S
Abstract: Background: Type 2 diabetes (T2D) is a rising global epidemic with lower socioeconomic status (SES) groups being more affected. Considering specific population subgroups to examine prevalence and SES inequalities in T2D is rare. In addition, using only one indicator to depict SES inequalities in health has been a common practice despite evidence on differences in what different indicators measure. This study examines the prevalence of and SES (school education, occupation and income) inequalities in T2D in the three population subgroups: employed individuals, nonworking spouses and pensioners. This study also determines the SES indictor with the highest explanatory power. Methods: This study is based on claims data from a statutory health insurance provider in Lower Saxony, Germany. T2D prevalence in the period between 2013 and 2017 was examined in 1, 345, 841 employed individuals, 180, 949 nonworking spouses and 773, 427 pensioners. Multivariate logistic regression analysis was applied to examine SES inequalities in T2D in the three subgroups. Explanatory power of the three SES indicators was compared by deviance analysis. Results: T2D prevalence was four times higher in male nonworking spouses (24.2%) and 2.6 times higher in female nonworking spouses (12.7%) compared to employed men (6.4%) and women (4.7%) respectively, while it accounted for 40% of men and 36% of women in pensioners. Clear gradients in T2D inequalities emerged for all three SES indicators and were observed in the three population subgroups. School education had the highest explanatory power in employed men and women and male nonworking spouses. Conclusions: Nonworking spouses are an important target group in T2D prevention interventions. The three SES indicators differ in their explanatory power where low school education appears to be a major risk factor. It can be discussed that health literacy and the associated health behavior play a role in mediating the association between education and T2D. Key messages: The population subgroup "nonworking spouses" is an important target group for type 2 diabetes prevention interventions. The level of school education is a substantial determinant of socioeconomic inequalities in type 2 diabetes.